background image

Theorem 9

1.

f

f

f

=

f

.

2.

f

f

f

=

f

.

Proof

1. Let

x

A

. We have

x

A

f

f

x

; consequently

f

x

B

f

f

f

x

. On the

other hand,

f

f

f

x

B

f

x

. So

f

f

f

x

=

f

x

.

2. Analogously.

Proposition 6

f

f

and

f

f

are idempotent.

Proof

f

f

is idempotent because

f

f

f

f

y

=

f

f

y

.

f

f

is similar.

Theorem 10

Each of two adjoints is uniquely determined by the other.

Proof

Let

p

and

q

be both upper adjoints of

f

. We have for all

x

A

and

y

B

:

x

p

(

y

)

f

(

x

)

y

x

q

(

y

)

.

For

x

=

p

(

y

) we obtain

p

(

y

)

q

(

y

) and for

x

=

q

(

y

) we obtain

q

(

y

)

p

(

y

). So

p

(

y

) =

q

(

y

).

Theorem 11

Let

f

be a function from a poset

A

to a poset

B

.

1. Both:

1. If

f

is monotone and

g

(

b

) = max

{

x

A

|

f x

b

}

is defined for every

b

B

then

g

is the upper adjoint of

f

.

2. If

g

:

B

A

is the upper adjoint of

f

then

g

(

b

) = max

{

x

A

|

f x

b

}

for every

b

B

.

2. Both:

1. If

f

is monotone and

g

(

b

) = min

{

x

A

|

f x

b

}

is defined for every

b

B

then

g

is the lower adjoint of

f

.

2. If

g

:

B

A

is the lower adjoint of

f

then

g

(

b

) = min

{

x

A

|

f x

b

}

for every

b

B

.

Proof

We will prove only the first as the second is its dual.

9